Application PAK RT Based Website Canva As Learning Media for Islamic Religious Education for Grade IV Elementary School - Diva Aura; Muhammad Reihanul Ilham; Yasmin Shabirah; Ani Nur Aeni (FASHLUNA, 2026)
Islamic Religious Education (PAI) learning in elementary schools often faces problems such as low student participation due to traditional teaching methods that make it difficult to access abstract materials. This study aims to develop an innovative learning medium in the form of a website-based application called "PAK RT" created using the Canva platform at SDN Pakuwon 2. Employing Research and Development (R&D) with the ADDIE model, this study involved 23 fourth-grade students in a limited trial. Data were collected through observation and student perception questionnaires, then analyzed using descriptive quantitative methods. The findings indicated high levels of user acceptance and satisfaction: 91.3% of students felt more motivated to participate in learning activities, and 95.7% acknowledged that the combination of text and video greatly helped them understand the material on the history of Prophet Muhammad's preaching. However, because this study did not employ pretests, posttests, control groups, or objective learning outcome measurements, the medium is categorized as feasible and promising for enhancing student interest and participation, but not empirically proven to improve learning achievement.